Diversification of production in order to improve competitiveness in the agribusiness trade agreements in Peru - Arroyo-Gordillo, Pedro (2016)
The study of diversifi cation in order to improve competitiveness in the trade agreements of Peru in the agribusiness sector are key within the challenge of innovation in the productive sector. The physical infrastructure defi cit presented by Peru does not allow the integration of markets nor the introduction of Peruvian companies to the global market. Therefore, management and public investment with private sector participation is required. The development of productive chains and clusters will contribute to the economic and social development of the Peruvian agroindustry.